Iggy Peck and the mysterious mansion - Beaty, Andrea (Beaty, Andrea. Questioneers, 2020)
Iggy is delighted when Ada Twist's Aunt Bernice inherits a mansion featuring his favorite architectural periods, but unless the Questioneers can find its missing antiques, the house may be lost forever. Includes information about Art Deco and Art Nouveau, facts about unusual cats, a recipe for ice cream, and a biographical note on Ida B. Wells